The biological productivity of natural forage plants` soils of Tersko-Sulakskaya lowland of Dagestan - M. E. Kotenko; M. A. Balamirzoev (Юг России: экология, развитие)
The present condition of soil cover and biological productivity of Tersko-Sulakskaya lowland’s forage plants is studied. The conducted investigations showed that overwrite forage plants on the salted soils have low forage productivity and nutritive value. The soils under it need a deep melioration measures.